Comprehension of business process models: Insight into cognitive strategies via eye tracking. (1st December 2019) - Tallon, Miles; Winter, Michael; Pryss, Rüdiger; Rakoczy, Katrin; Reichert, Manfred; Greenlee, Mark W.; Frick, Ulrich
Highlights: Students understand Process Models in configurative patterns. A homogeneous continuously distributed competence level can be rejected. Activities labelled by single letters (not sentences) support model comprehension. Needless wording prolongs respective fixation time. Process Model comprehension does not seem to depend too much on Visual Literacy. Abstract: Process Models (PM) are visual documentations of the business processes within or across enterprises. Activities (tasks) are arranged together into a model (i.e., similar to flowcharts). This study aimed at understanding the underlying structure of PM comprehension. Though standards for describing PM have been defined, the cognitive work load they evoke, their structure, and the efficacy of information transmission are only partially understood. Two studies were conducted to better differentiate the concept of visual literacy (VL) and logical reasoning in interpreting PM. Study I: A total of 1047 students from 52 school classes were assessed. Three different process models of increasing complexity were presented on tablets. Additionally, written labels of the models' elements were randomly allocated to scholars in a 3-group between-subjects design. Comprehension of process models was assessed by a series of 3 × 4 (=12) dichotomous test items. Latent Class Analysis of solved items revealed 6 qualitatively differing solution patterns, suggesting that a single test score is insufficient to reflect participants' performance. Study II: Overall, 21 experts and 15 novices with respect to visual literacy were presented the same set of PMs as in Study I, while wearing eye tracking glasses. The fixation duration on relevant parts of the PM and on questions were recorded, as well as the total time needed to solve all 12 test items. The number of gaze transitions between process model and comprehension questions was measured as well. Being an expert in visual literacy did not alter the capability of correctly understanding graphical logical PMs. Presenting PMs that are labelled by single letters had a significant influence on reducing the time spent on irrelevant model parts but did not affect the fixation duration on relevant areas of interest. Both samples' participants required longer response times with increasing model complexity. The number of toggles (i.e., gaze transitions between model and statement area of interest) was predictive for membership in one of the latent classes. Contrary to expectations, denoting the PM events and decisions not with real-world descriptions, but with single letters, led to lower cognitive workload in responding to comprehension questions and to better results. Visual Literacy experts could neither outperform novices nor high-school students in comprehending PM.